Perancangan Aplikasi Ensiklopedia Ilmuwan Islam Berbasis Android dengan Metode Crochemore Perrin - Fitria Fitria (Universitas Budi Darma, 2019)
Encyclopedia in the form of a number of writings that contain explanations that store information comprehensively and quickly understood and understood. Scientists generally mean intelligence and knowledge in a field arranged systematically according to the rules and methods that can be used to explain and explain and understand things related to the field of scientists. One solution to solve the problem of searching for Android-based Islamic scientists with the Crochemore Perrin method. To simplify the process of searching strings on Android-based Islamic scientist encyclopedias. By applying the Perrin Crochemore algorithm to the Android-based Islamic scientist search system, the process of searching for Islamic scientists is easier and faster. The system is designed very practical because it uses an Android application. So it can be accessed anywhere.